European Peace Facility : what is the role of European security provider in the war of Ukraine? - Tellaeche García, Beatriz Diana (My University, 2022)
El objetivo principal de ese trabajo de fin de grado es entender la guerra en Ucrania, y el papel que desempeña el Fondo Europeo de Apoyo a la Paz, internacionalmente conocido como el European Peace Facility, en la invasión rusa en Ucrania.

The aim of this dissertation is to understand the War in Ukraine as well as to shed light on the role of the European Peace Facility in the Russian invasion of Ukraine.
Grado en Relaciones Internacionales y Grado en Comunicación Internacional - Bachelor in Global Communication
Keywords: 59 Ciencia política; 5901 Relaciones internacionales; 590103 Política internacional; K2R